The Flâneur’s Scopic Power or the Victorian Dream of Transparency - Estelle Murail (Cahiers Victoriens et Edouardiens)
This article focuses on the dream of transparency which pervaded the nineteenth-century literary cityscape, and which, I argue, is embodied in the figure of the flâneur, the ubiquitous observer of urban life. To shed light on the function and makeup of this enigmatic figure, I analyze the flâneur through the lens of transparency and through the prism of three objects which use transparency as their core functioning principle. I start by considering the idea that the flâneur is akin to a transparent glass pane. However, a closer look at the flâneur reveals him to be far from simply transparent. Beholding him through the lens of a stereoscope brings his multi-layered nature into relief. This paper concludes by examining the flâneur’s vision, which could be said to function like a spyglass. For the flâneur, being ‘transparent’ in the city is ultimately translating modernity through his gaze, footsteps, and words. To see and to give solidity to the dream of transparency, transparency cannot be absolute, but must be mediated and filtered through the opacity of writing.